2008
DOI: 10.1186/1746-6148-4-49
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of importance for human health in Nigerian dogs: high prevalence and limited knowledge of pet owners

Abstract: BackgroundDogs are the most common pet animals worldwide. They may harbour a wide range of parasites with zoonotic potential, thus causing a health risk to humans. In Nigeria, epidemiological knowledge on these parasites is limited.MethodsIn a community-based study, we examined 396 dogs in urban and rural areas of Ilorin (Kwara State, Central Nigeria) for ectoparasites and intestinal helminths. In addition, a questionnaire regarding knowledge and practices was applied to pet owners.ResultsNine ectoparasite spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
72
5
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 41 publications
25
72
5
5
Order By: Relevance
“…The high prevalence of these parasites found in this study represents an important risk to develop some of these parasitic diseases in the human population. The endoparasite T. vulpis was more prevalent than reported by other studies carried out in rural areas from Nigeria (14.2%) and the Czech Republic (1.7%) (DUBNÁ et al, 2007;UGBOMOIKO et al, 2008). In Argentina, Soriano et al (2010) reported a prevalence of 1.3% in rural areas of Neuquén.…”
Section: Discussioncontrasting
confidence: 48%
“…The high prevalence of these parasites found in this study represents an important risk to develop some of these parasitic diseases in the human population. The endoparasite T. vulpis was more prevalent than reported by other studies carried out in rural areas from Nigeria (14.2%) and the Czech Republic (1.7%) (DUBNÁ et al, 2007;UGBOMOIKO et al, 2008). In Argentina, Soriano et al (2010) reported a prevalence of 1.3% in rural areas of Neuquén.…”
Section: Discussioncontrasting
confidence: 48%
“…The association observed in the present study between age < 1 year and parasitic infections was expected and it was related to the biology of the parasite and the host immune status (FONTANARROSA et al, 2006;LABRUNA et al, 2006;KATAGIRI & OLIVEIRA-SEQUEIRA, 2008;UGBOMOIKO et al, 2008;MOHAMED et al, 2009). The factors of age over one year, mixed breed, male gender and lack of anthelmintic use were associated with occurrences of Ancylostoma spp.…”
Section: Discussionmentioning
confidence: 70%
“…In the Czech Republic (DUBNÁ et al, 2007), Nigeria (UGBOMOIKO et al, 2008), USA (MOHAMED et al, 2009) and Argentina (SORIANO et al, 2010), all three of these nematodes were present, but T. canis showed the highest prevalence. In Venezuela (RAMÍREZ-BARRIOS et al, 2004), Colombia (GIRALDO et al, 2005) and Argentina (FONTANARROSA et al, 2006), like in the present study, Ancylostoma spp.…”
Section: Discussionmentioning
confidence: 99%
“…(Ramıŕez-Barrios et al 2004); in Africa in Ethiopia (Zewdu et al 2010, Jones et al 2011 and Nigeria (S. stercoralis and Strongyloides sp.) (Ugochukwu & Ejimadu 1985, Ugbomoiko et al 2008; in Asia in Iran (Razmi 2009), South Korea (Yang et al 2013 and Japan (Itoh et al 2003, Asano et al 2004, Itoh et al 2009); and in Australia (Bugg et al 1999). Focusing on the cases so far diagnosed in Iceland none originated from this part of the world, but it should be noted that relatively few dogs brought to Iceland originated in these geographical areas.…”
Section: Discussionmentioning
confidence: 99%